A study of relationship between job satisfaction and individual equity sensitivity among employees in MBZ Engineering Enterprise / Syafiqa Idora Ibrahim - Ibrahim, Syafiqa Idora (2014)
MBZ Engineering Enterprise is a company based on electrical and mechanical company. This business actually is a partnership with 3 sharing partners. MBZ Engineering is a small local company was established almost 8 years, and have 50 employees. This company provides the service for wiring, repairing of plumbing, CCTV, air-conditioning units and more about electrical and mechanical. However, the main business for this company is selling, service and repairing air-conditioning unit. The main vendor for supply the air-conditioning unit is York Company, and MBZ Engineering as a dealer. In this company their employee has been complaining about how they are rewarded differently. Then, the turnover rate in this company was really high, this is because they perceived that the salary, reward and benefits is not equal to their contributions for the company. This is why some of them have low levels of job satisfaction. So, this research is conducted to investigate if there is a relationship between job satisfaction and individual’s perceived equity in their contributions for the organization. In this research have 50 respondents as the sampling research from the population in that company also has 50 employees. This research was conducted to study about the relationship between job satisfaction and equity sensitivity individuals among employee in this company. This research has used questionnaire and previous journals as the data sources of data. The questionnaires has distributed to all the respondents to collect the data, then enter the data into Statistical Package for Social Sciences (SPSS) software for data analysis. Researcher has used the frequency analysis, reliability, descriptive and correlation analysis as the data collection method. From the result, the benevolent individual has high job satisfaction, entitled has no job satisfaction and equity sensitive also has job satisfaction but lower than benevolent.